Network Plasticity Involved in the Spread of Neural Activity Within the Rhinal Cortices as Revealed by Voltage-Sensitive Dye Imaging in Mouse Brain Slices - Kajiwara, Riichi; Tominaga, Yoko; Tominaga, Takashi (Frontiers in Cellular Neuroscience, 2019)
The rhinal cortices, such as the perirhinal cortex (PC) and entorhinal cortex (EC), are located within the bidirectional pathway between the neocortex and the hippocampus. Our previous study indicated that an increase in excitability in deep layers of the PC/EC border is critical for neural activity transfer from the PC to the EC. In the present study, we hypothesized that such changes in network dynamics are not incidental observations but rather due to the plastic features of the PC-EC network. To confirm this idea, we analyzed the network properties of the neural transmission throughout the rhinal cortices and the plastic behavior of the network by performing a single-photon wide-field optical recording technique with a voltage-sensitive dye in mouse brain slices that contained the PC, EC, and hippocampus. The depolarized response evoked by 40-Hz electrical stimulation delivered to the superficial layers of the PC spread across a wide area of the PC under partial suppression of the γ-aminobutyric acid (GABA) A system. However, this experimental procedure did not cause the spread of neural activities across the border of the PC/EC. Next, we examined the effect of 4-aminopyridine (4-AP) on PC-EC transmission. 4-AP enhanced neural activity in the PC, which eventually propagated to the EC via the deep layers of the PC/EC border. Interestingly, washout of 4-AP was unable to reverse the entorhinal activation. The changes in the network properties persisted for more than one hour. We confirmed that a similar phenomenon was observed without treatment with 4-AP by applying repeated burst stimulation to the neurons in the perirhinal deep layers. This procedure facilitates neural propagation across the border under partial suppression of GABA-A inhibition. Therefore, once PC-EC transmission occurred, even stimulation of the superficial layers, which was previously ineffective at initiating PC/EC transmission, allowed for effective neural transmission to the EC. These observations might be due to plasticity in the PC-EC network.